2019
DOI: 10.15581/003.32.1.313-331
|View full text |Cite
|
Sign up to set email alerts
|

Audiovisual content with advertising intention in children's videos on YouTube: the case of the Soy Luna series

Abstract: Advertising on the web has taken new forms (Malin, 2011; Susarla, Oh & Tan, 2012). In this context, videos which appear playful but which have an advertising objective, have positioned themselves as the new trend (Craig & Duncan, 2017; Marsh, 2015) and have penetrated the web space for an increasing number of Internet users, particularly among children (Davies, Coleman & Livingstone, 2014). However, the type and variety of videos with advertising intention that YouTube leads users to when searching for generic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 12 publications
0
3
0
5
Order By: Relevance
“…Given that influencers generate interest and are followed through social media, this leads brands to want to count them in when implementing new ways of advertising [39]. Now, faced with this phenomenon, it is worth asking about the ability minors have to identify the persuasive intentionality of the messages they receive from the influencers they follow on social networks, that is, their level of advertising literacy [40] especially in the face of content that increasingly mixes advertising and entertainment [41,42]. Previous studies have researched the recognition of advertising on social networks by minors and have concluded that these generally identify standard formats as advertising, but more camouflaged commercial messages are not considered as such (unboxing or recommendations from YouTubers and Instagrammers) [43].…”
Section: Discussionmentioning
confidence: 99%
“…Given that influencers generate interest and are followed through social media, this leads brands to want to count them in when implementing new ways of advertising [39]. Now, faced with this phenomenon, it is worth asking about the ability minors have to identify the persuasive intentionality of the messages they receive from the influencers they follow on social networks, that is, their level of advertising literacy [40] especially in the face of content that increasingly mixes advertising and entertainment [41,42]. Previous studies have researched the recognition of advertising on social networks by minors and have concluded that these generally identify standard formats as advertising, but more camouflaged commercial messages are not considered as such (unboxing or recommendations from YouTubers and Instagrammers) [43].…”
Section: Discussionmentioning
confidence: 99%
“…los contenidos Publicitarios en redes sociales Los contenidos de marca que aparecen prescritos por los kid influencers en sus canales, sin aviso de publicidad, es uno de los aspectos más inquietantes en los que respecta a YouTube (Tur-Viñes et al, 2019;Feijoo & Pavez, 2019). Es necesario promover una regulación eficaz que permita diferenciar los contenidos comerciales del resto (IAB Spain, 2019).…”
Section: La Generación De Los Kid Influencersunclassified
“…Los riesgos derivan de la dificultad de las personas de menor edad para identificar la intención publicitaria, la inexistencia de advertencias por una regulación imprecisa, y la percepción de credibilidad otorgada a los comerciales del youtuber (Tur-Viñes et al, 2018;Feijoo & Pavez, 2019). Niños y niñas influyentes en YouTube e Instagram metodología Esta investigación analizó el tipo de contenidos publicado, la presencia de marcas y las técnicas publicitarias empleadas en los videos, y su posible asociación con la temática del confinamiento o del Covid19, de trece niños y niñas influyentes, menores de 14 años y de habla española, en sus canales de YouTube e Instagram durante el primer periodo de confinamiento en España (14 de marzo al 26 de abril de 2020).…”
Section: La Generación De Los Kid Influencersunclassified
See 2 more Smart Citations